PROPAGANDA HAK ANGKET DPR TERHADAP KPK (Analisis Propaganda dan Komunikasi Politik) - Yopi Perdana Kusuma (Universitas Serang Raya, 2017)
The investigation of the E-KTP case that dragged some members of DPR led to the formation of Pansus Hak Angket KPK. Instead of exploring information about the function of eradicating corruption, the formation of Pansus Hak Angket KPK is tend to be political propaganda in improving the image of DPR. This can be seen from how the using of vertical communication channel (especially through the mass media) rather than the horizontal communication channel. Moreover, the initial goal of Pansus Hak Angket KPK is to urge KPK to open a recording of the examination of Miryam Haryani who became a suspect in the case of E-KTP. This research uses qualitative methods to disquss the propaganda of DPR against KPK. With descriptive method, this research is to describe what and how propaganda DPR against KPK. From the various issues raised by Pansus Hak Angket KPK, it is seen how the formation of Pansus is irrelevant, because the existing problems can be solved through working meetings between DPR and KPK. Meanwhile, the communication channels tend to be more done vertically (especially through the mass media) rather than horizontally. In addition, DPR as a political communicator does not have adequate credibility in conducting propaganda against KPK. The public is also more confident of KPK rather than DPR. This research concludes that the formation of Pansus Hak Angket is full of political interests, became a political propaganda to improve the image of DPR and to strike down KPK rather than seeking truth or strengthening KPK. Keywords: Political Propaganda, DPR-RI, Hak Angket, KPK, Combating Corruption.